Keselamatan dan kesihatan pekerja asing di Sarawak :kajian kes buruh Indonesia - Siti Fatimah, Anak Ngalai (Universiti Malaysia Sarawak, UNIMAS, 2010)
This aim of this study is to investigate safety and health of foreign workers in the factory and marketing sectors. A safe working environment will increase the quali ty and image of organizations because practices on safe working environment decrease accidental cost . The researcher compared the research findings with previous findings from other communities and with the relevant theories such as Maslow’s Theory, Accide nt Domino’s Theory, and Human Factors Theory. The findings of this research show that human s play a important role in order to avoi d unpredictable accident happening in the workplace. This research is a qualitative and the researcher use d unstructured inte rview s to what data same findings about safety and health factors , surr ounding environments, culture, person s who are involved in safety and health of workers and the environment that influenced safety and health of the workers. The findings of this stud y give an indication about aspects of safety and health that must be taken seriously by organizations , su pervisors and workers .